A situational analysis of current antimicrobial governance, regulation, and utilization in South Africa. (November 2017) - Schellack, Natalie; Benjamin, Deon; Brink, Adrian; Duse, Adriano; Faure, Kim; Goff, Debra; Mendelson, Marc; Meyer, Johanna; Miot, Jacqui; Perovic, Olga; Pople, Troy; Suleman, Fatima; et al.
Highlights: Reliable antimicrobial consumption data for developing countries are limited. Alternative mechanisms of assessing antimicrobial consumption data could be used, e.g. procurement and tender data. Antimicrobial utilization data could be used to guide antimicrobial stewardship strategies. Abstract: The Global Action Plan on antimicrobial resistance calls for the use of antimicrobial medicines in human and animal health to be optimized, in tandem with a strengthening of the knowledge and evidence base through surveillance and research. However, there is a paucity of consumption data for African countries such as South Africa. Determining antimicrobial consumption data in low-resource settings remains a challenge. This article describes alternative mechanisms of assessing antimicrobial consumption data, such as the use of Intercontinental Marketing Services (IMS) data and contract data arising from tenders (an open Request for Proposal, RFP), as opposed to the international norms of daily defined doses per 100 patient-days or per 1000 population. Despite their limitations, these serve as indicators of antimicrobial exposure at the population level and represent an alternative method for ascertaining antimicrobial consumption in human health. Furthermore, South Africa has the largest antiretroviral treatment programme globally and carries a high burden of tuberculosis. This prompted the inclusion of antiretroviral and anti-tuberculosis antibiotic consumption data. Knowledge of antimicrobial utilization is imperative for meaningful future interventions. Baseline antimicrobial utilization data could guide future research initiatives that could provide a better understanding of the different measures of antibiotic use and the level of antibiotic resistance.